Political appointees vs. elected officials: Examining how the selection mechanism for state governing agency board members influences responsiveness to stakeholders in higher education policy-making - Rubin, Paul G. (Education Policy Analysis Archives, 2021)
Through an exploratory comparative case study of two U.S. states (Georgia and Nevada), this study investigates how the selection mechanism to state higher education governing agency boards influences the responsiveness of board members to stakeholders and their role in the policy-making process. Framed around the recent national policy agenda to improve postsecondary degree attainment and college completion, findings suggest that state agency board members in both states prioritized the opinions, insights, and goals of the state governor and governing agency staff, regardless of selection mechanism. However, for more localized issues and on-the-ground decision-making, stakeholders formally involved in the day-to-day operation of higher education, such as administrators, faculty, and students, serve a larger role, though this influence can be mediated by the selection mechanism of board members.